2016
DOI: 10.5424/sjar/2016141-7169
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the mediating role of trust in food products with Protected Designation of Origin. The case of ´Jamón de Teruel´

Abstract: The growing concern about quality in food products has substantially increased the competitiveness of agro-food products that possess quality-system certifications compared to non-certificated products. This research focused on understanding how consumer trust is greater when agro-food products have a Protected Designation of Origin (PDO). In particular, we analyze whether the influence of consumers’ perceived quality of a PDO product has a direct effect on their perceived risk or whether this relationship is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In line with previous studies, were identified consumers that consider that the food quality is not verified [25,26]. Thus, there are consumers that trust the meaning of these certifications and choose to buy a more traditional healthy food product [20,21,23,24,35,66].…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, these products are often associated with a clear delimited geographical area [19]. On the other hand, consumers from central and northern Europe tend to focus mainly on practical issues, such as convenience, health, or the ease and speed of purchasing food [24]. Some consumers consider PDO/PGI labels to be organic, while every second consumers are unsure whether PDO/PGI certified foods are produced without fertilizers and other chemicals [25,26].…”
Section: Perception About Certified Agri-food Productsmentioning
confidence: 99%
“…Consumers’ decision-making processes around food are complex, dynamic and multidimensional. Recent trends in consumer attitudes and behaviour include an increased focus on food safety and health, partly as a result of high-profile food crises and alarms, new information about diet and health as well as consumer concerns about the application of new technologies in the food sector [ 1 , 2 , 3 , 4 , 5 ]. In addition, traditional purchasing criteria such as price and taste continue to be important [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, previous studies in gilthead sea bream clearly indicate that the inclusion of vegetable oils in fish feeds reduced the content of LC-PUFAs and increased that of C18 PUFAs in liver, adipose tissue and muscle fillets, with a selective incorporation of unsaturated FAs in polar lipids (Izquierdo et al, 2005;Benedito-Palos et al, 2010; to preserve and maintain the function of cell membrane surfaces. Especially for fat fish species, most of these changes in the flesh FA composition are highly predictable by means of a dummy regression model (Ballester-Lozano et al, 2014;2016). Less is known about the effects of diet composition on the FA composition of circulating lipids, although overall they also reflect the changes in diet composition (Laidlaw and Holub, 2003;Lemaitre et al, 2003) as it was herein the case of circulating PCs, lysoPCs and free FAs.…”
Section: Elucidation Of Untargeted Differential Compoundsmentioning
confidence: 99%
“…In last few years, research efforts have been directed towards the identification of PDO chemomarkers for premium food products, such as Extra Virgin Olive Oil , Saffron (Rubert, Lacina, Zachariasova, & Hajslova, 2016), Spanish 'Jamón de Teruel' (Fandos-Herrera, 2016) , Vinegars (Chinnici, Durán-Guerrero, & Riponi, 2015) , Wines or Brazilian coffee (Nagai, Santini Pigatto, & Lourenzani, 2016). In the field of coffee authentication, studies have been reported for variety discrimination (Montero-Vargas et al, 2013) as well as specialty processing like Asian palm civet coffee (Jumhawan et al, 2013) due to its high market prize and taste.…”
Section: Iii3: Artículo Científico 5 Introductionmentioning
confidence: 99%